“Determinación de los parámetros de diseño de un transportador de banda para la agroindustria de granos” - Días Guilca, Edgar Xavier (2019)
The present work was carried out for the reception and silage line of the Agroindustrial Grain Company “Fernando Echenique”, Combate del Cerro Enterprise Basic Unit (UEB), from Bartolomé Masó, Granma province. This enterprise belongs to the Agroindustrial Rice Complex (CAI) Fernando Echenique. The objective of the investigation was directed to determine the designing parameters for the belt conveyor to guarantee the transportation of rice to the storage silos. For this purpose, a methodology based on the basic foundations of the design of Machine Elements, specifically in the continuous transport, was developed, which is reported within the specialized literature. Among the main results, there are some relevant data concerning the width of the belt equal to 400 mm, the actual speed equal to 1.03 m s-1, effective draft equal to 4 811.45 kg, required power equal to 53.99 kW and the number of layers equal to 3. As a conclusion, it is obtained that with the proposed belt conveyor, benefits in the technological and economic order will be obtained, due to the fact that the interruptions during the productive process will be eliminated as a consequence of the lack of raw material in the silos.